57 The effect of remote ischemic conditioning and glyceryl trinitrate on perioperative myocardial injury in cardiac bypass surgery patients: the eric-gtn study. (5th October 2017) - Hamarneh, A; Hardman, E; Wicks, P; Shanahan, H; Bulluck, H; Ramlall, M; Chung, R; Bell, R; Cordery, R; Yellon, D; Hausenloy, D
Abstract : Introduction: Remote Ischaemic Conditioning (RIC) using transient limb ischemia/reperfusion has been reported to reduce peri-operative myocardial injury (PMI) in patients undergoing coronary artery bypass grafting (CABG) and/or valve surgery. The role of intravenous Glyceryl Trinitrate (GTN) therapy administered during cardiac surgery as a cardioprotective agent and whether it interferes with RIC cardioprotection is not clear and is investigated in the ERIC-GTN trial (Clinicaltrial.govidentifier:NCT01864252 ). Aims: The ERIC-GTN trial has been designed to determine whether intraoperatively administered IV GTN is cardioprotective during cardiac surgery and to investigate the interaction between RIC and IV GTN in their cardioprotective effects. Hypothesis 1 : Intra-operative intravenous GTN will reduce PMI in patients undergoing CABG and/or valve surgery. Hypothesis 2 : RIC will reduce PMI in the absence of GTN in patients undergoing CABG and/or valve surgery. Hypothesis 3 : RIC will not reduce PMI in the presence of GTN in patients undergoing CABG and/or valve surgery. Design: The ERIC-GTN trial is a single site, double-blind, randomised placebo-controlled study. Consenting adult patients (>18 years) undergoing elective CABG ±valve surgery with blood cardioplegia will be eligible for inclusion. 260 patients will be randomised to one of four treatment groups following aesthetic induction: (1) RIC alone : RIC protocol comprising three 5-minutes cycles of simultaneous upper arm and thigh cuff inflation/deflation followed by an intravenous (IV) placebo infusion; (2) GTN alone : A simulated sham RIC protocol will be applied followed by an IV GTN infusion; (3) RIC+ GTN : RIC protocol followed by IV GTN infusion; and (4) Neither RIC or GTN : Sham RIC protocol followed by IV placebo infusion. The primary endpoint will be peri-operative myocardial injury as quantified by the 72 hour area-under-the-curve (AUC) serum high sensitive Troponin-T. Implication: The ERIC-GTN trial will determine whether intra-operative GTN therapy is cardioprotective during cardiac surgery, and whether it affects RIC cardioprotection. We recruited 180 out of 260 patients so far and are currently undertaking a pre-specified interim analysis.